Paper Electronics: Laser‐Induced Molybdenum Carbide–Graphene Composites for 3D Foldable Paper Electronics (Adv. Mater. 26/2018). Issue 26 (22nd June 2018) - Zang, Xining; Shen, Caiwei; Chu, Yao; Li, Buxuan; Wei, Minsong; Zhong, Junwen; Sanghadasa, Mohan; Lin, Liwei
Abstract : In article1800062, Xining Zang, Liwei Lin, and co‐workers develop a direct‐write laser‐patterning technology to engrave random shapes of metal‐carbide–graphene composites (MCG) on different types of paper (A4, wiper, filter paper, etc.). These commercial papers are soaked with solutions containing metal ions in gelatin media, which is the major component of "jelly". Highly conductive and multifunctional MCG–paper substrates are applied in a 3D foldable energy generator, electrochemical sensors, and supercapacitors.